2018
DOI: 10.21931/rb/2018.03.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Determinación de coeficientes de degradación de materia orgánica en el rio Negro (municipio de Rionegro, Colombia)

Abstract: Determinación de coeficientes de degradación de materia orgánica en el rio Negro (municipio de Rionegro, Colombia). Determination of kinetics coefficients of organic matter degradation in Negro river (municipality of Rionegro, Colombia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…On the other hand, the points from P6 to P8 showed low BOD values from 0.25 to 0.85 mg/L in the rainy season, while in the dry season the values reached up to 28.69 mg/L. These areas have a high populational density and in most cases the wastewater and solid waste are thrown off into the river, which favors the increase of BOD [39].…”
Section: DL (Detection Limit)mentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, the points from P6 to P8 showed low BOD values from 0.25 to 0.85 mg/L in the rainy season, while in the dry season the values reached up to 28.69 mg/L. These areas have a high populational density and in most cases the wastewater and solid waste are thrown off into the river, which favors the increase of BOD [39].…”
Section: DL (Detection Limit)mentioning
confidence: 96%
“…In P1, P2 and P3, it is observed that the BOD is not detectable (< D.L.) (Table 6), since around these points there are no dwellings that can produce waste, there are low agricultural and livestock production, and little presence of vegetation, therefore a low presence of carbonaceous matter [39]. Regarding P4 and P5 (from 2916 to 2872 m of altitude), these points have a low populational density, but they develop intensive agricultural and livestock activities, using pesticides and herbicides without control [6], whose residues are transported to the river by runoff or irrigation of residual water, considerably affecting the microflora and microfauna of river water, which could inhibit the decomposition and degradation of the organic matter [40,41]; this same behavior occurs in P8 in the dry season.…”
Section: DL (Detection Limit)mentioning
confidence: 99%